Whose art is it? - Kramer, Jane 1938- (Public planet books, 1994)
"Whose Art Is It? is the story of sculptor John Ahearn, a white artist in a black and Hispanic neighborhood of the South Bronx, and of the people he cast for a series of public sculptures commissioned for an intersection outside a police station. Jane Kramer, telling this story, raises one of the most urgent questions of our time: How do we live in a society we share with people who are, often by their own definitions, "different?" Ahearn's subjects were "not the best of the neighborhood." They were a junkie, a hustler, and a street kid. Their images sparked a controversy throughout the community - and New York itself - over issues of white representations of people of color and the appropriateness of particular images as civic art. The sculptures, cast in bronze and painted, were up for only five days before Ahearn removed them." From the bookjacket.